Upaya Hukum Terhadap Perselisihan Status Kepemilikian Tanah Adat Menjadi Hutan Lindung Di Kecamatan Batudaa Kabupaten Gorontalo - Nusi, Andri; Junus, Nirwan; Bakung, Dolot Alhasni (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
Customary land/ulayat land is a large area of ​​land that is jointly owned by a clan or tribe. Protected forest is a forest whose existence is protected because it is useful in maintaining the ecosystem. The designation of a forest area to become a protected forest is based on the function of the forest as a provider of clean water reserves, erosion control, habitat for flora and fauna, and other functions. There are still many conflicts between indigenous peoples and the government and many have not been resolved, so that indigenous peoples are not free to cultivate their land. The purpose of this study is to find out what are the legal remedies for disputes over ownership status of customary land to become protected forest in Batudaa sub-district. The method used in this study is a qualitative method with a descriptive approach. The results of the research are that the efforts made to settle this land dispute are with the community getting an SKT from the government.